Current Concepts in Extra-articular Impingement of the Hip: Clinical Diagnosis, Imaging, and Treatment - Koles, Sarah L.; Salat, Peter; Veljkovic, Andrea; Marín-Peña, Óliver; Kassarjian, Ara (Seminars in Musculoskeletal Radiology, 2017)
Hip impingement syndromes, particularly femoroacetabular impingement syndrome, have attracted tremendous attention in the past decade. We address some of the less common hip impingement syndromes, mainly the extra-articular hip impingement syndromes. The clinical presentation, imaging, and treatment of anterior, posterior, and lateral hip impingement syndromes are discussed.
Keywords: hip impingement; sports MRI; subspine deep gluteal syndrome